2019
DOI: 10.1021/acs.energyfuels.8b04040
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Abnormal Combustion in Direct Injection Spark Ignition Engines Using Conventional and Alternative Fuels

Abstract: In this paper, the potential of alternative fuels to reduce preignition in engines is primarily investigated. Two ketones (2-butanone and 3-methylbutanone), a furan (2-methylfuran), and five alcohols (ethanol, iso-propanol, 2-butanol, iso-butanol, and 1-propanol) are compared to three conventional fuels (RON95E0, RON95E10, and iso-octane). If the alternative fuels can reduce preignition significantly, the efficiency of spark-ignition engines can be potentially increased. One major aim is to categorize the fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
2
2
0
Order By: Relevance
“…Tests were performed from 8:1 for pure gasoline to 16:1 for E84 blend. These results are in accordance with previous studies 29,3032…”
Section: Introductionsupporting
confidence: 94%
See 2 more Smart Citations
“…Tests were performed from 8:1 for pure gasoline to 16:1 for E84 blend. These results are in accordance with previous studies 29,3032…”
Section: Introductionsupporting
confidence: 94%
“…Tests were performed from 8:1 for pure gasoline to 16:1 for E84 blend. These results are in accordance with previous studies 29,[30][31][32] Qian et al 34 demonstrated that the knock-limited spark timing can be advanced progressively as the ethanol injection proportion is increased as well. Tests were carried out in a dual-fuel SI engine.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…Super-knock phenomenon and mitigation strategies has been discussed in detail by previous works. [15][16][17][18][19] In addition, studies [20][21][22] have reported preignition potential of various fuels and blends. Despite the high resistance to auto-ignition of ethanol, the longer injection duration and wall wetting increases pre-ignition occurrences that could lead to super-knock.…”
Section: Introductionmentioning
confidence: 99%